Rising Wage Inequality in Germany - Johannes Gernandt; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The paper investigates the evolution of wages and wage inequality in Germany based on samples from the German Socio-Economic Panel (GSOEP) 1984 to 2005. Real gross hourly wages for prime age dependent male workers increased on average by 23 percent between 1984 and 1994 in West Germany and the wage distribution was fairly stable. Between 1994 and 2005 average wages increased by 7 percent in West Germany and 18 percent in East Germany. In this period wage inequality, measured by the ratio of the ninetieth to tenth percentile of the wage distribution, increased from 2.5 to 3.1 in West Germany and from 2.4 to 3.2 in East Germany. In West Germany rising wage inequality occurred mainly in the lower part of the wage distribution, whereas in East Germany wage inequality predominantly increased in the upper part of the wage distribution. In West Germany the group of workers with low tenure experienced higher increases in wage inequality compared to the group of workers with high tenure.
Older version: http://hdl.handle.net/10419/24211
Keywords: J31; J24; J21; 330; Wage Inequality; Skill Structure; Real Wages; Tenure; Lohnstruktur; Einkommensverteilung; Betriebszugehörigkeit; Qualifikation; Schätzung; Theorie; Alte Bundesländer; Neue Bundesländer